DESIGN OF DIDACTIC SYSTEM FOR DEVELOPMENT OF TECHNICAL COMPETENCE OF 6-7 YEAR-OLD CHILDREN - Garnevska, S.M (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2020)
This article is dedicated to the introduction of technical equipment as an object of study by preschool children. The possibilities for development of technical competence in children in a preparatory group are studied. A didactic system aimed at developing technical competence has been developed. The content includes the following topics: Topic 1: Tools - children distinguish tools that are used in different activities by people with different professions, realizing role-playing games. Topic 2: Household appliances - children acquire knowledge about household appliances and their safe use by modeling them with waste materials. Topic 3: Space walk - modeling with folds of cardboard to obtain a model of a technical object (air vehicle). Topic 4: Crossroads - mastering the rules and regulations for safe movement on the road by modeling a crossroads. Topic 5: Laptop - introduction to modern communication technologies and tools, laptop modeling, observations in a real work environment using a computer and laptop. Topic 6: Robots - кnowledge of technical progress and robots as a modern technical tool by modeling. Topic 7: Transformers - the formation of interest in technology through the design of toys, carriers of modern technology. Topic 8: Clock - making a model of a clock from a metal constructor using real technical tools (screwdriver, wrench). The organization of the activity is commented. Conclusions are formulated about the importance and efficiency of the created didactic system.